2008
DOI: 10.1093/pcp/pcn128
|View full text |Cite
|
Sign up to set email alerts
|

Various Spatiotemporal Expression Profiles of Anther-Expressed Genes in Rice

Abstract: The male gametophyte and tapetum play different roles during anther development although they are differentiated from the same cell lineage, the L2 layer. Until now, it has not been possible to delineate their transcriptomes due to technical difficulties in separating the two cell types. In the present study, we characterized the separated transcriptomes of the rice microspore/pollen and tapetum using laser microdissection (LM)-mediated microarray. Spatiotemporal expression patterns of 28,141 anther-expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
94
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 46 publications
7
94
0
Order By: Relevance
“…According to the RiceGE (Gene Expression Atlas Data Sources), PTC1 expression is highest in the 10-to 15-cm inflorescence (stages 7-10), gradually decreasing in the 15-to 20-cm inflorescence (stages 10-12; http://signal.salk.edu/ cgi-bin/RiceGE). Recent expression profile data from laser microdissection coupled with microarray analysis also suggest that PTC1 is expressed in both the tapetum and microspores at stage 8 (Hobo et al, 2008). Consistent with this, our reverse transcription (RT)-PCR and quantitative RT-PCR (RT-qPCR) results indicated that PTC1 was preferentially expressed in the anther from stage 8 to stage 9 (Fig.…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microsposupporting
confidence: 85%
See 1 more Smart Citation
“…According to the RiceGE (Gene Expression Atlas Data Sources), PTC1 expression is highest in the 10-to 15-cm inflorescence (stages 7-10), gradually decreasing in the 15-to 20-cm inflorescence (stages 10-12; http://signal.salk.edu/ cgi-bin/RiceGE). Recent expression profile data from laser microdissection coupled with microarray analysis also suggest that PTC1 is expressed in both the tapetum and microspores at stage 8 (Hobo et al, 2008). Consistent with this, our reverse transcription (RT)-PCR and quantitative RT-PCR (RT-qPCR) results indicated that PTC1 was preferentially expressed in the anther from stage 8 to stage 9 (Fig.…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microsposupporting
confidence: 85%
“…Since PTC1 expression is specific to the tapetum and microspores, the ptc1 data were compared with the laser microdissection- coupled microarray data of wild-type rice microspores/pollen and the tapetum (Hobo et al, 2008). We identified 1,569 down-regulated genes and 848 upregulated genes (2,417 in total) with a change in expression of 2-fold or more in the tapetum and/or microspores at stages 8 and 9 between the wild type and ptc1 (Supplemental Data Set S1).…”
Section: Ptc1 Is Preferentially Expressed In the Tapetum And Microspomentioning
confidence: 99%
“…heat stressed pistil pollinated with fresh pollen and vice versa wherein female reproductive organ did not reduce fertility even with 40 C exposure, whereas pollen exposed to 38 C led to a significant decline in spikelet fertility (Yoshida et al 1981). Further, the majority of the physiological or molecular studies dealing with microsporogenesis have drawn conclusions based on a single genotype (Kerim et al 2003;Hobo et al 2008;Oliver et al 2005Oliver et al , 2007Endo et al 2009). We hypothesise that spikelet size (length) coinciding with microsporogenesis varies with genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on certain research tools, such as mutant identification, gene expression differences analysis and comparative genomics, a number of pollen development related genes associated with each process in rice were identified and cloned. For example, MSP1 gene expressed in surrounding cells of male and female sporocytes and some flower tissues, controlling the primary wall cells and primary sporogenous cell development in rice (Nonomura et al, 2003); OsRad21-4 continuously expressed from before microspore mother cells meiosis to meiosis stages, participating in meiosis homologous chromosomes pairing and sisters chromosome synapsis ; PAIR1 and PAIR2 gene expressed mainly at the microspore mother cells meiotic stages and played an essential role in establishment of homologous chromosome pairing in rice meiosis (Nonomura et al, 2004a;Nonomura et al, 2004b); OsPBP1 protein was a novel functional C2-domain phospholipids-binding protein and localized in a region peripheral to pollen wall and vesicles of elongating pollen tube (Yang et al, 2008); RA68 expressed persistently from the pollen mother cell differentiation to mononuclear microspore stages and might be required for postmeiotic pollen development by affecting pollen mitosis Ⅰ and starch accumulation ; RIP1 was most active at the late binucleate microspore and trinucleate microspore stages, which probably carried out an important role during the late stage of pollen formation ; Osnop gene expressed only in late stage of pollen development with the highest expression at the stage of pollen release and germination, and then probably cross-linked both calcium and phosphoinositide signaling pathways (Jiang et al, 2005); AID1 controled the normal maturation pollen grains and anther dehiscence, as well as increased tillering and early flowering (Zhu et al, 2004); however, comparing with a great deal of genes in the pollen development process (Hobo et al, 2008;Suwabe et al, 2008), pollen development molecular mechanisms are still at an exploratory stage. Thus deep investigation in this area will present practical and theoretical significance.…”
Section: Introductionmentioning
confidence: 99%